The Potential and Reality of New Refugees Entering German Higher Education: The Case of Berlin Institutions. Issue 4 (2nd October 2017) - Streitwieser, Bernhard; Brueck, Lukas; Moody, Rachel; Taylor, Margaret
Abstract : By the close of 2015, roughly 890, 000 new refugees had arrived in Germany, more than half fleeing the ongoing Syrian Civil War. While Germany had been accustomed to heavy migration streams since the end of the Second World War, the speed of the refugee influx was unexpected. Federal, state, and municipal governments and German civil society, including educational institutions, were largely unprepared and scrambled to respond. This article critically examines the efforts of three universities in Berlin to address the "refugee crisis, " with additional data from higher education experts at ministries, foundations, and institutes in Berlin and Bonn, Germany. The Campus Crisis Management framework developed by Zdziarski, Dunkel, and Rollo is used to critically investigate their response and its implications for Germany.